An improved homogenization method for the treatment of strong absorbers in pebble-bed HTGR. (1st June 2022) - Wen, Yutong; She, Ding; Shi, Lei
Highlights: An improved homogenization method is proposed to treat the strong absorbers in the HTGR reflector. Numerical results show good accuracy and applicability of the improved model. The method has been implemented in PANGU code, improving the code's accuracy in HTGR absorbers reactivity worth calculation. Abstract: In pebble-bed high temperature gas-cooled reactors (HTGRs), strong absorbers including control rods and absorber balls are placed in the reflector. The strong absorber regions need to be homogenized for the convenience of downstream whole-core neutronics diffusion calculation. Previously, a homogenization method based on the generalized equivalence theory (GET) was studied. This paper proposes an improved homogenization method by employing a more rigorous discontinuity factor (DF) model, for more accurate treatment of the strong absorbers in the HTGR reflector. The proposed method has been implemented in the PANGU code developed by Institute of Nuclear and New Energy Technology (INET), Tsinghua University. Numerical results suggest that the newly proposed homogenization method achieves good agreement with the heterogeneous Monte Carlo transport solution and experimental result.